Doctor Who. Twice upon a time [videorecording (DVD)] - Capaldi, Peter; Mackie, Pearl, 1987-; Gatiss, Mark (Doctor Who., 2018)
This Christmas, the Doctor comes face to face with, the Doctor! The first and current Doctors contemplate mortality in the Arctic as the join forces against a common enemy, revisit another last-of-its-kind being, and are ultimately responsible for the life of a WWI soldier.